GROWTH AND YIELD OF Asystasia gangetica (L) SUBSP. MICRANTHA THE FERTILIZED WITH A MIXTURE OF COW MANURE AND GRAPE WASTE - G. A.,, Sulendra,; Kusumawati,, N. N. C.; Witariadi., N. M. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
Asystasia gangetica (L) subsp. Micrantha The benefits of eating livestock from nutrition, body strength, palatability are many. from the quality that increases to the optimality of this plant by using organic fertilizer from a mixture of grape waste and cow dung to reduce the use of inorganic fertilizer. This study is targeted at observing development of plant objects. Micrantha is fertilized using a mixture of cow dung and grape waste. This assessment was held in Sading Village, in Rumah Kaca, Badung Regency, Mengwi District, for up to 12 weeks from preparation to cutting. The series of trials from the RAL/complete random sequence of 5 attitudes 6 tests, a total of 30 combinations were tried. Action as follows: A: 100% cow dung, B: 100% grape waste, C: 75% cow dung + 25% grape waste, D: 50% cow dung + 50% grape waste, and E: 25% cow dung + 75% grape waste. This study looks at each variable that has been determined to be studied. The results of the study of applying this mixed fertilizer can increase the total height of a plant's leaves for weight dryness. A conclusion is formed if the development of Asystasia gangetica (L) subsp. Micrantha is influenced by a mixture of cow dung + grape waste, and a fertilizer mixture of 25% cow dung + 75% grape waste provides development of the object The best micrantha.